Selected Extensions on Eneström-kakeya Theorem - et. al., R. K. Pavan Kumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The theorem of Eneström-Kakeya is important within the hypothesis of dissemination of zeros ofpolynomials. In the literature, it can be found so many extensions on Eneström-Kakeya theorem by giving various relations between the coefficients of polynomial like increasing, decreasing, irregular order etc.This paper mainly deals with some extensions on the Abdul Aziz and B AZargar theorembygiving some relaxations to the hypothesis that the coefficients are real, positive and alternative coefficients must be in increasing order.